Outcome of Cyanoacrylate Glue Injection for Bleeding Gastric Varices - Baral, Shankar; Thapa, Suresh; Regmi, Kiran; Thapa, Jiwan; Pokharel Baral, Anjila (Nepal Journal of Medical Sciences, 2024)
Introduction: Gastric variceal bleeding is catastrophic and difficult to manage. Use of N-butyl-2-cyanoacylate (NBCA) is recommended for bleeding gastric varices but the data on efficacy and complications are variable. Hence our study has assessed the outcome of endoscopic NBCA injection in bleeding fundal varices. Methods: We prospectively analyzed 24 patients of bleeding gastric varices between April 2023 to March 2024 who were treated with N Butyl 2-Cyanoacrylate. Repeated injections were done on single sessions or multiple sessions as required till the varices were solidified properly. Patients demographic profile, initial endoscopic findings, volume (sessions) of glue used and complications were recorded. Results: A total of 24 patients were treated with glue injection. Mean age was 52.6±14.8years and 15(62.50%) were males. Cirrhosis was the major cause for gastric variceal bleeding in 20 patients (83.33%) and ethanol consumption 13(54.17%) was the major cause of liver cirrhosis. Majority of gastric variceal bleeding were due to GOV2 23(95.83%) followed by IGV1 in 1(4.17%). Haemostasis was achieved in 13(54.17%) cases with 1 ml of NBCA injection, while 9(37.50%) of patients needed 2 ml and 2(8.33%) needed 3 ml. We achieved complete hemostasis in 19(79.2%) patients in one session and rest needed a second session. Sixteen patients (66.7%) did not have any complications. One patient had major complication with mesenteric vein thrombosis however rest developed minor complications including pain abdomen in 7(29.17%) and post injection site ulcer noted in 3(12.5%). Conclusions: N-butyl-2-cyanoacylate (NBCA) also called Glue injection for bleeding gastric varices is highly effective even with a single session with minimal complications.